Sosialisasi dan Penyerahan Rancangan Cold Storage sebagai Tempat Penyimpanan Hasil Panen Urban Farming “MOM’S FARM” di Kampung Nagrek - Suprata, Ferdian; Surbakti, Feliks P.S; Tampubolon, Victoria P.L.K (Program Studi Teknik Industri, Fakultas Teknik, Universitas Katolik Indonesia Atma Jaya Jakarta, 2021)
Obstacles found in urban farming include vegetables that are not durable and perishable before being consumed, marketed, or further distributed to the nearest markets or retailers. The activity aimed to inform and share cold storage design to store the harvesting